(untitled) (Літератури світу: поетика, ментальність і духовність, 2016)
The following article is on the Oxana Zabuzhko’s creative work philosophy analysis (based on the «The Alien Woman» story). Rejecting the socialist-realist concept the writer tends to romantic interpretation of the artist role and the sources of creative work. Explication of the postmodern philosophema «death of the author» in Zabuzhko’s works occurs at the level of poetics.